A case report of temple squamoid eccrine ductal carcinoma: A diagnostic challenge beneath the tip of the iceberg. Issue 2 (12th January 2020) - Phan, Kevin; Kim, Leo; Lim, Penny; Cheung, Karen
Abstract: Eccrine carcinomas are a rare tumor entity which originates from eccrine glands and comprise <0.01% of all cutaneous tumors. Eccrine carcinoma subtypes are classified based on their distinct histopathological pattern. Squamoid eccrine ductal carcinoma (SEDC) is a rare subtype, characterized by both squamous and adnexal ductal differentiation, and resembles squamous cell carcinoma on clinical examination. Given the rarity of these tumors, there remains a lack of clear diagnostic criteria or treatment guidelines for the management of SEDC. We report a rare case of SEDC with perineural invasion in an elderly gentleman who was treated with wide local excision.